2020
DOI: 10.3390/f11090920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Combination of Moderate-Temperature Heat Treatment and Subsequent Wax Impregnation on Wood Hygroscopicity, Dimensional Stability, and Mechanical Properties

Abstract: Wood is an environmentally friendly material, but some natural properties limit its wide application. To study the effect of a combination of heat treatment (HT) and wax impregnation (WI) on wood hygroscopicity, dimensional stability, and mechanical properties, samples of Pterocarpus macrocarpus Kurz wood were subjected to HT at a moderate temperature of 120 °C and a high temperature of 180 °C, for a 4 h duration. Subsequently, half of the 120 °C HT samples were treated with WI at 90 °C. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…This indicated that thermal modification of wood had a negative effect on the mechanical properties of the coating applied to TMWs and became worse with the increase in temperature of thermal modification. This was because wood extraction had a positive effect on the coating while the thermal modification reduced the content of wood extraction [49,50]. The components of the lower molecular weight of the coating embedded the CWs of TMWs after being coated, and the resin interacted with the extractions in the cell wall ultimately leading to the difference in mechanical properties.…”
Section: Nanoindentation (Ni)mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that thermal modification of wood had a negative effect on the mechanical properties of the coating applied to TMWs and became worse with the increase in temperature of thermal modification. This was because wood extraction had a positive effect on the coating while the thermal modification reduced the content of wood extraction [49,50]. The components of the lower molecular weight of the coating embedded the CWs of TMWs after being coated, and the resin interacted with the extractions in the cell wall ultimately leading to the difference in mechanical properties.…”
Section: Nanoindentation (Ni)mentioning
confidence: 99%
“…In the process of thermal modification, the lignin condensation via cross-linking reactions with furfural set free from hemicelluloses, which may have contributed to the increase in the cellulose crystallinity index of the wood [51]. In addition, it is possible that the cross-linking reaction between CWs and the molecules of the coating also played an important role in improving the E r and H of CWs [49,50]. Figure 8 illustrates the Er of the coating and cell walls at different locations of the natural wood and on the cross-sections of TMW samples.…”
Section: Nanoindentation (Ni)mentioning
confidence: 99%
“…At the same time, considering that wood contains cellulose, hemicellulose, lignin, starch, sugar, and other components, it is a hotbed for microbial growth [ 31 , 32 ]. When the temperature and humidity and other environmental conditions are appropriate, these microorganisms will attach to the wood for a large number of growth and reproduction, resulting in wood decay, discoloration, and moldy, which influence the strength, toughness, and permeability of wood [ 6 , 33 , 34 , 35 ]. It also poses a threat to the life and health of the users [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have conducted some valuable works on the effects of factors that influencing the fracture mechanical properties of wood materials, such as temperature [20,21], testing method [22], moisture content [23][24][25][26][27], wood species [26,28,29], fracture modes [30], cracking system [30], etc. These studies provided fundamental data for characterizing wood fracture behaviors.…”
Section: Introductionmentioning
confidence: 99%